Green Intellectual Capital and Competitive Advantage, and Sustainable MSMEs: Is Tri Hita Karana Important? - Desak Nyoman Sri Werastuti; Anantawikrama Tungga Atmadja; I Made Pradana Adiputra (Accounting Study Programme Faculty of Economics and Business Universitas Negeri Surabaya, 2025)
Research Background: Companies worldwide now face the challenge of not only generating profits but also ensuring sustainability in their business practices. Introduction / Objectives: The purpose of this study is to analyze the impact of green intellectual capital on competitive advantage with Tri Hita Karana as a moderator. Methods: The SEM-PLS analysis method was used. The sample of this study was fashion MSMEs operating in Bali. Results: This study found that green intellectual capital contributes significantly to competitive advantage. However, Tri Hita Karana only moderates the effect of green structural capital on competitive advantage. Conclusion: This finding suggests that local cultural values ​​strengthen sustainable organizational infrastructure and systems in business practices. This finding emphasizes the importance of integrating local cultural values ​​into the intellectual capital-based view theory. Corporate policies need to support sustainability to strengthen competitiveness.